Analisis Yuridis Akta Perdamaian Perjanjian Kerjasama Penglolaan Barang Milik Negara (Perjanjian Antara Pusat Koperasi TNI Angkatan Darat Dengan PT Luwiwan Megah Perkasa) - Azli Akbar Albanna; Maria Kaban; Suatiarnoto Suatiarnoto; Abd Harris (Fakultas Hukum Universitas Al Azhar Medan, 2023)
The focus of this research is a case that happened between Koperasi TNI Angkatan Darat (Indonesian Army Cooperative) and PT Luwiwan Megah Perkara in connection with the management of Sriwijaya Sports Centre which fall under the category of state-owned assets. The assets stand on a state-owned land with management rights in the form of Right to Use Certificate on the name of Ministry of Defense of the Republic of Indonesia. The management of the asset was in the form of Build Operate Transfer (BOT) agreement. The Koperasi TNI Angkatan Darat (Indonesian Army Cooperative) itself is an independent legal entity and not structurally under the auspice of the Indonesian army. The main problems on this research are: 1) the legal standing of Koperasi TNI Angkatan Darat (Indonesian Army Cooperative) in entering into a management agreement of state-owned assets; and 2) Legal analysis of the claim submitted by PT Luwiwan Megah Perkasa against Koperasi TNI Angkatan Darat (Indonesian Army Cooperative). This research is normative legal research, with the nature of descriptive analysis research. The approach used is the statutory approach. The theory of agreement, theory of authority, and legal protection theory are used to analyze the main problems in this research